Room Temperature Electrical and Thermal Switching CNT/Hexadecane Composites. (15th July 2013) - Sun, P. C.; Wu, Y. L.; Gao, J. W.; Cheng, G. A.; Chen, G.; Zheng, R. T.
Abstract : A large contrast in the electrical and thermal conductivities via a first order phase transition in surface‐functionalized carbon nanotube(CNT)/hexadecane composites is reported. Surface modification of the CNTs improves the electrical conductivity contrast and the stability of the composites. We demonstrate that, with these composites, the electrical conductivity changes above 10 5 times and the thermal conductivity varies up to 3 times at 18 °C.